Disruption of mitochondrial membrane potential coupled with alterations in cardiac biomarker expression as early cardiotoxic signatures in human ES cell–derived cardiac cells. (September 2019) - Jyoti, Saras; Tandon, Simran
Cardiotoxicity is one of the most significant reasons of attrition in drug development. The present study assessed the sensitivity of various endpoints for early monitoring of drug-induced cardiotoxicity using human embryonic stem cell–derived cardiac cells, including precursors as well as mature cardiomyocytes, by correlating changes in cardiac biomarker expression. Directed differentiation was induced and cardiac progenitor cell (CPC) population were treated with cardiotoxic drugs, namely, doxorubicin (Dox) and paclitaxel (Pac), and with noncardiotoxic drug, namely penicillin G. To assess cardiac-specific toxicity, the changes in the expression of key markers of cardiac lineage, such as Nkx2.5, Tbx5, α -myosin heavy chain α-MHC, and cardiac troponin T, were studied using quantitative real-time polymerase chain reaction (qRT-PCR) and flow cytometry (FC). The half-maximal inhibition in the expression of these cardiac markers was analyzed from the dose–response curves. We also assessed the half-maximal inhibition (IC50 ) in cardiac cells using propidium iodide dye (IC50 PI) and by measuring disruption in the mitochondrial membrane potential (IC50 MMP). We observed that the most sensitive marker was α-MHC in the case of both Dox and Pac, and the order of sensitivity of the various prediction assays was MMP > protein expression by FC > gene expression by qRT-PCR > cell viability by PI staining. The results could enrich the screening of drug-induced cardiotoxicity in vitro and propose disruption in MMP along with downregulation of α -MHC protein as a potential biomarker of predicting cardiotoxicity earlier during drug safety evaluation.